Research-based interventions in the area of proof: The past, the present, and the future. - Stylianides, G; Stylianides, A (Springer, 2017)
The concept of proof has attracted considerable research attention over the past decades in part due to its indisputable importance to the discipline of mathematics and to students’ learning of mathematics. Yet the teaching and learning of proof is an instructionally arduous territory, with proof being recognized as a hard-to-teach and hard-to-learn concept at all levels of education. Prior research has examined, documented, and cast light on the processes underpinning different problems of classroom practice in the area of proof, but has paid less emphasis on acting upon such problems to generate possible solutions through research-based interventions in mathematics classrooms. In this Editorial we first situate the contributions in this Special Issue in a brief chronological account of scholarly work on research-based interventions in the area of proof and we conclude with a proposal for some high-leverage directions for future research.